Influence of Life Diet on the Biology and Demographic Parameters of Agistemus olivi Romeih, a Specific Predator of Eriophyid Pest Mites (Acari: Stigmaeidae and Eriophyidae) - Faten Mamdouh Momen, (Tropical Life Sciences Research, 2012)
The influence of various life diets on the biology and demographic parameters of the predatory mite, Agistemus olivi Romeih, was studied under laboratory conditions. A. olivi successfully developed and reproduced on all of the tested eriophyid mites. Feeding on Aceria mangiferae Sayed enhanced the development of A. olivi, resulted in the shortest mean generation time and was the most commensurate food for the ovipostion of the predator, as exhibited by the highest fecundity and net reproductive rate. Preying on Aculops lycopersici (Massee) gave the lowest fecundity and net reproductive rate; therefore, this prey was the least suitable for the oviposition of A. olivi. Preying on Aculus fockeui (Nalepa et Trouessart) and A. mangiferae produced higher intrinsic rates of increase and finite rates of increase for the predator in comparison to A. lycopersici, which showed the lowest value. These differences in response to various eriophyid pests should be considered for the production of healthy cultures of A. olivi. Pengaruh pelbagai diet hidup terhadap parameter biologi dan demografik pemangsa hama, Agistemus olivi Romeih, telah dikaji di makmal. A. olivi telah berjaya membiak dalam setiap hama eriophyid yang telah dikaji. A. olive yang makan Aceria mangiferae Sayed mengalami peningkatan pertumbuhan, yang menyebabkan masa generasi min yang terpendek dan merupakan makanan yang paling sesuai untuk oviposisi pemangsa, seperti yang telah ditunjukkan oleh nilai fecunditi dan kadar pembiakan. Memakan Aculops lycopersici (Massee) telah memberikan nilai fecunditi dan kadar pembiakan yang terendah; maka mangsa ini merupakan yang paling tidak sesuai untuk oviposisi of A. olivi. Memakan Aculus fockeui (Nalepa et Trouessart) dan A. mangiferae telah menghasilkan kadar peningkatan instrisik dan finite yang lebih tinggi untuk pemangsa berbanding dengan A. lycopersici, yang telah menunjukkan nilai yang terendah. Perbezaan ini perlu diambil kira untuk produksi kultur sihat A. olivi.